Taking the Bite Out of Winter: Common Murres (Uria aalge) Push Their Dive Limits to Surmount Energy Constraints - Burke, Chantelle M.; Montevecchi, William A. (Frontiers in Marine Science, 2018)
Diving seabirds that overwinter at high latitudes experience persistent cold exposure, shorter days and associated declines in ocean productivity that can challenge their ability to balance daily energy budgets. We used dive-immersion geo-locators to test the hypothesis that pursuit-diving Common murres (Uria aalge) will respond to the challenges of winter in the North Atlantic through increased daily energy expenditures (DEE) that will be met by increased foraging effort and adjustments in dive tactics. Largely flightless in winter (< 5% of daylight hours flying), murres spent most of their time on the water (> 85% resting and swimming). Accordingly, when sea surface temperatures (SST) were consistently near freezing in late winter (1.9 ± 0.8 °C), mean DEE (2463.2 ± 10.9 kJ day-1) exceeded the theoretical limit to sustainable energy expenditure in vertebrates (i.e. 7 X Basal Metabolic Rate or 2450 kJ day-1 for murres). Consistently deep (70% > 50m) and long dives in late winter, 38% of which exceeded their calculated aerobic dive limit indicate that targeted prey was distributed in deep (dark) waters. Consequently, foraging was highly constrained to daylight hours; likely because capture efficiency of deep-water prey is very poor in low light. Murres responded to late winter time and energy constraints with a nearly 2-fold increase in daily time spent diving (95.2 ± 5.6 mins and 178.3 ± 6.3 mins day-1 during early and late winter, respectively), an increase in dive bout frequency and duration, and correspondingly less time resting between bouts. Uniquely adapted for deep-diving, pursuit-diving murres push their dive limits in order to maximize daily energy intake when energy demands are high and prey are distributed in deep water. This study highlights late winter as an extremely challenging phase in the annual cycle of North Atlantic murres and provides critical insights into the behavioral mechanisms underlying their winter survival.